In vitro and in vivo antitumor activity of Yerba Mate extract in colon cancer models. Issue 7 (22nd June 2020) - Garcia‐Lazaro, Rocio S.; Lamdan, Humberto; Caligiuri, Lorena G.; Lorenzo, Norailys; Berengeno, Andrea L.; Ortega, Hugo H.; Alonso, Daniel F.; Farina, Hernan G.
Abstract : Abstract: Yerba Mate ( Ilex paraguariensis St. Hill. Aquifoliaceae ) is a native South American tree and has a large amount of bioactive compounds. Colorectal cancer (CRC) is one of the so‐called westernized diseases and is the third most common cancer in both men and women. Efficient strategies for the treatment of CRC are extensively being explored including dietary intervention. The objective of our research was to evaluate the effects of Yerba Mate extract on cell proliferation, invasive capacity of tumor cells, and angiogenesis. For this, in vitro and in vivo experimentation was carried out using CRC models. The extract was generated by aqueous extraction and prepared according to traditional American procedure of preparing mate infusion. In vitro results showed that the Yerba Mate extract inhibits CT26 and COLO 205 cell proliferation with IC50 values of 0.25 and 0.46 mg/mL, respectively. We demonstrated by TUNEL assay that one of the mechanisms by which Yerba Mate extract decreases cell proliferation is by induction of apoptosis. In a murine syngeneic tumor model, oral administration of Yerba Mate extract in a dose of 1.6 g/kg/day significantly inhibited angiogenesis and tumor growth without affecting biological parameters or body weight. Our findings suggest that Yerba Mate may be a promising agent for the treatment of colon cancer and could be used as an herbal medicine or functional food ingredient. Practical Application: Considering the chemical composition and presence of phenolic compounds with their free‐radical scavenging activities and bioactivities against colon cancer cells, Yerba Mate can be a promising candidate as healthy food sources in human nutrition, and also be considered a natural source of potential antitumor agents. Taking into account the economic importance of Yerba Mate in Argentina, this vegetable would have a greater commercial value as a functional food.